Contextual determinants of CHILDREN'S health care and policy in Europe - Kinga Zdunek; Peter Schröder-Bäck; Denise Alexander; Michael Rigby; Mitch Blair (BMC, 2019)
Abstract Background The main objective of this study was to explore the contextual determinants of child health policies. Methods The Horizon 2020 Models of Child Health Appraised (MOCHA) project has one Country Agent (CA) in all 30 EU and EEA countries. A questionnaire designed by MOCHA researchers as a semi-structured survey instrument asked CAs to identify and report the predominating public and professional discussions related to child health services within the last 5 years in their country and the various factors which may have influenced these. The survey was issued to CAs following validation by an independent Expert Advisory Board. The data were collected between July and December 2016. The data was qualitatively analysed using software Nvivo11 for data coding and categorization and constructing the scheme for identified processes or elements. Results Contextual determinants of children's health care and policy were grouped into four categories. 1) Socio-cultural determinants: societal activation, awareness, communication, trust, freedom, contextual change, lifestyle, tolerance and religion, and history. 2) Structural determinants which were divided into: a) external determinants related to elements indirectly correlated with health care and b) internal determinants comprising interdependent health care and policy processes. 3) International determinants such as cross-nationality of child health policy issues. 4) The specific situational determinants: events which contributed to intensification of debates which were reflected by behavioural, procedural, institutional and global factors. Conclusions The influence of context across European countries, in the process of children's health policy development is clearly evident from our research. A number of key categories of determinants which influence child health policy have been identified and can be used to describe this context. Child health policy is often initiated in reaction to public discontentment. The multiple voices of society resulted, amongst others, in the introduction of new procedures, action plans and guidelines; raising levels of awareness, intensifying public scrutiny, increasing access and availability of services and provoking introduction of structural changes or withdrawing unfavourable changes.